A host-coupling bio-nanogenerator for electrically stimulated osteogenesis. (September 2021) - Yu, Bin; Qiao, Zhiguang; Cui, Jinjie; Lian, Meifei; Han, Yu; Zhang, Xing; Wang, Weiqi; Yu, Xingge; Yu, Hao; Wang, Xudong; Lin, Kaili
Abstract: Implantable self-powered generators (ISPGs) have been extensively explored as energy supplies for driving electronics and electrically stimulated therapeutics in vivo . However, some drawbacks arise, such as complicated architectonics, inescapability of wire connection, energy instability, and consumption. In this study, a host-coupling bio-nanogenerator (HCBG) is developed to configure a self-powered regional electrical environment for powerful bone regeneration. An HCBG consists of a porous electret nanofiber mat coupled with interstitial fluid and stimulated objects of the host after implantation, forming a host coupling effect. This bio-nanogenerator not only overcomes the disadvantages of general ISPGs, but also accomplishes both biomechanical energy scavenging and electrical stimulation therapeutics. The enhancement of osteogenesis differentiation of bone marrow mesenchymal stem cells in vitro and bone regeneration in vivo are remarkably achieved. Moreover, osteogenic ability is systematically evaluated by regulating the electrical performance of HCBGs. Osteogenic differentiation is activated by upregulating more cytosolic calcium ion, following to activate the calcium ion-induced osteogenic signal pathway, while applying electrical stimulation. As an implantable medical technology, the HCBG provides an explorative insight to facilitate the development of ISPG-based electrical medical therapeutics.